Extracorporeal Methods of Detoxification in Generalized Peritonitis - O. M. Shevtsova; N. V. Shapovalova; A. A. Lavrentyev; T. V. Beloshevskaya; V. N. Mishchuk (Общая реаниматология)
Objective: to optimize the results of treatment in patients with generalized peritonitis. Sixty-eight patients were examined. In Group 1 (n=26), plasmapheresis was performed during traditional therapy; in Group 2 (n=28) plasmapheresis was combined with extracorporeal antibiotic therapy; and Group 3 (n=12) received only traditional therapy (a control group). The parameters of hemostasis, endotoxemia, and immunity were studied over time. The early use of these methods improved hemostatic parameters and mortality rates. Key words: generalized peritonitis, plasmapheresis, extracor-poreal pharmacotherapy.